An introduction to the “Li Spicy Unit” for the pungency degree of spicy foods - De-Jian Li; Yan-Fei Li; Hong-Jun Li; De-Cai Zhou; Chong-Xia Hu; Ren-You Gan; Harold Corke; Hua-Bin Li; Li Zhang (International Journal of Food Properties, 2020)
Spicy foods are very popular in many countries of the world, but there is still a lack of a simple and intuitive unit to characterize the pungency degree of spicy foods. In this study, the pungency degrees of Spicy Hotpot were evaluated by a large-scale consumer testing, and six levels of pungency degree were graded and connected with contents of main capsaicinoids (CMC) in Spicy Hotpot, from which a new unit of pungency degree was established, the “Li Spicy Unit” (LSU), with the equation: LSU = 10.369 ln (CMC) + 65.264. In addition, it was found that LSU was also suitable for evaluating the pungency degree of several other spicy foods. Therefore, LSU can be a good indicator of the pungency degree of diverse spicy foods. The new LSU can provide an easy tool for public education to help consumers pick spicy foods with a suitable pungency degree.